Fast identification of lipase inhibitors in oolong tea by using lipase functionalised Fe3O4 magnetic nanoparticles coupled with UPLC–MS/MS. (15th April 2015) - Zhu, Yuan-Ting; Ren, Xiao-Yun; Yuan, Li; Liu, Yi-Ming; Liang, Jian; Liao, Xun
Highlights: Lipase inhibitors present in oolong tea were investigated by a facile method. Lipase-magnetic nanoparticles were used to extract enzyme inhibitors. Fast identification of lipase inhibitors was achieved with UPLC–MS. Three enzyme inhibitors were selectively and simultaneously extracted out. This study improves understanding of mechanism for health benefit of oolong tea. Abstract: Oolong tea is an important member in tea family, which claims for various health benefits such as preventing obesity and improving lipid metabolism. In this work, using pancreatic lipase (PL) functionalised magnetic nanoparticles (PL-MNPs) as solid phase extraction absorbent in combination with ultra-high performance liquid chromatography–mass spectrometry (UPLC–MS), we developed a method for rapid screening and identification of lipase inhibitors from oolong tea. Three PL ligands were selectively extracted and identified as (−)-epigallocatechin-3- O -gallate (EGCG), (−)-gallocatechin-3- O -gallate (GCG) and (−)-epicatechin-3- O -gallate (ECG). Their lipase inhibitory activities were significantly higher than those non-ligands. Structure–activity analysis revealed that the presence of a galloyl moiety in the structure was required for binding to PL-MNPs, and therefore, exhibiting a strong inhibition on the enzyme. Taking advantages of the specificity in enzyme binding and the convenience of magnetic separation, this method has great potential for fast screening of lipase inhibitors from natural resources.